2021
DOI: 10.1016/s0378-4274(21)00564-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, health recovery by medicinal plants (health solutions): An overview

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Purpose: In the treatment of patients with COVID-19, various drug combinations have been used and the full effectiveness of them is not certain. Therefore, at this time, the role of secondary metabolites and active ingredients of medicinal plants such as phenolic compounds, flavonoids, alkaloids and terpenoids and their effect in the treatment of cancer, inflammatory diseases and microbial pathogens cannot be ignored [ 1 , 2 , 3 ]. In this study, the effectiveness of this type of treatment in a patient with COVID-19 was shown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Purpose: In the treatment of patients with COVID-19, various drug combinations have been used and the full effectiveness of them is not certain. Therefore, at this time, the role of secondary metabolites and active ingredients of medicinal plants such as phenolic compounds, flavonoids, alkaloids and terpenoids and their effect in the treatment of cancer, inflammatory diseases and microbial pathogens cannot be ignored [ 1 , 2 , 3 ]. In this study, the effectiveness of this type of treatment in a patient with COVID-19 was shown.…”
mentioning
confidence: 99%
“…Methods: The treatment protocol was infusing 20 g of a mixture of dried plants included; Thymus vulgaris, Mentha pulegium, Hyssopus officinalis, Ziziphus jujuba, Althea officinalis, Verbascum thapsus, Malva sylvestris and Stachys lavandulifolia (250 mg/kg of body weight/day) in 400 ml of water [ 1 ]. Brewing time was set at half an hour.…”
mentioning
confidence: 99%